CD99 Drives Terminal Differentiation of Osteosarcoma Cells by Acting as a Spatial Regulator of ERK 1/2. (May 2014) - Sciandra, Marika; Marino, Maria Teresa; Manara, Maria Cristina; Guerzoni, Clara; Grano, Maria; Oranger, Angela; Lucarelli, Enrico; Lollini, Pier‐Luigi; Dozza, Barbara; Pratelli, Loredana; Renzo, Maria Flavia Di; Colombo, Mario Paolo; et al.
ABSTRACT Differentiation therapy is an attractive treatment for osteosarcoma (OS). CD99 is a cell surface molecule expressed in mesenchymal stem cells and osteoblasts that is maintained during osteoblast differentiation while lost in OS. Herein, we show that whenever OS cells regain CD99, they become prone to reactivate the terminal differentiation program. In differentiating conditions, CD99‐transfected OS cells express osteocyte markers, halt proliferation, and largely die by apoptosis, resembling the fate of mature osteoblasts. CD99 induces ERK activation, increasing its membrane‐bound/cytoplasmic form rather than affecting its nuclear localization. Through cytoplasmic ERK, CD99 promotes activity of the main osteogenic transcriptional factors AP1 and RUNX2, which in turn enhance osteocalcin and p21WAF1/CIP1, leading to G0/G1 arrest. These data underscore the alternative positions of active ERK into distinct subcellular compartments as key events for determining OS fate. © 2014 American Society for Bone and Mineral Research.